Microsurgical management of posterior cerebral artery aneurysms: A report of thirty cases in modern era. (June 2015) - Wang, Wen-Xin; Xu, Bai-Nan; Wang, Fu-Yu; Wu, Chen; Sun, Zheng-Hui
Abstract Objective. We reviewed a series of 30 cases of posterior cerebral artery (PCA) aneurysms to examine the outcomes of microsurgical techniques, which is an important alternative to endovascular interventions in localities where access to the latter renders practical difficulty. We also aimed to introduce the initial experience about the clinical application of intraoperative computed tomography (CT) in treatment of PCA aneurysm. Methods. Thirty patients with PCA aneurysm treated using microsurgery in our department between January 1996 and July 2014 were reviewed retrospectively. Results. The case series included 13 females and 17 males with a mean age of 44 years, ranging from 8 to 78 years. Eighteen aneurysms were ruptured, five aneurysms caused a direct mass effect, and the remaining seven aneurysms were found incidentally. Most aneurysms were located in the P1 segment or the P1–P2 junction of the PCA (63%). Eighteen aneurysms (60%) were large or giant in size (≥10 mm). Seventeen aneurysms were directly clipped, six trapped, one wrapped, one electrocoagulated and resected, and five trapped or proximal clipped with a bypass. Intraoperative perfusion CT (PCT) and CT angiography (CTA) were applied to provide immediate information regarding cerebral hemodynamics and anatomy of vessels in six patients. Twenty-six patients (87%) showed good clinical outcomes according to the modified Rankin Scale score (≤2) at the mean clinical follow-up period of 34 (range: 1–78) months, including the patients using intraoperative CT, and one (3%) patient was dead. Conclusion. Microsurgical therapy for patients with PCA aneurysms can have a positive outcome with correctly selected techniques. Personalized microsurgical treatment paradigms are determined by the anatomical location, shape and size of the PCA aneurysm, and the clinical features of the patient. Intraoperative PCT and CTA can improve the efficacy of the surgical treatment.